Evaluation of Ecological Minimum Quantity Lubrication Turning of AISI 4340 Alloy for Parametric Choices Using the Distance from Average Solution (EDAS) Method - Ozule, Chukwuka Prosper; Oke, Sunday Ayoola; Rajan, John; Oluwo, Adeyinka; Oyekeye, Manasseh Olusegun (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
Flood-cutting fluids and minimum quantity lubrication (MQL) schemes are associated with high cutting fluid costs and health effects, which should be regulated through the selection and optimization of parameters. This paper applies the distance from average solution (EDAS) method to assess the criteria value regarding three alternatives (cutting depth, cutting speed and feed) using CuO nano lubricants discharged in minimum quantity lubrication. Three responses, including beneficial (cutting speed, feed and cutting depth) and non-beneficial (cutting force) responses were used. A novel weight determination scheme based on the beneficial and non-beneficial criteria was established for the first time as inputs to the EDAS method. The weights established 0.1504, 0.2832, 0.2832 and 0.2832 for cutting force, cutting speed, feed and cutting depth, respectively. The results show a multi-modal best performance of 0.8438, which occurs in multiple experimental trials of 2, 4, 5, and 8. The optimization implemented in this study uses all inputs and the CuO nano lubricant was considered in each case using a spreadsheet for the evaluation. Case study data illustrating the uniqueness of the method using the literature data shows that EDAS is robust enough to be applied in machining activities.